Photoelectrochemical Hydrogen Generation Using C-dot/ZnO Hierarchical Nanostructure as an Efficient Photoanode. Issue 6 (1st January 2015) - Kim, Heejin; Kwon, Woosung; Choi, Mingi; Rhee, Shi-Woo; Yong, Kijung
Abstract : In this study, we have developed a stable and environmental-friendly photoelectrode of carbon nanodots (C-dots) coupled with a 3 dimensional ZnO structure. Our C-dots are synthesized hydrothermally with a high yield of 40%, and they are successfully anchored onto the ZnO backbone via a facile solution procedure. The as-prepared C-dot/ZnO photoelectrodes have exhibited reasonable photocurrent density and remarkable photostability under the 1 sun irradiation condition without any sacrificial reagent. We have studied the chemistry beneath the C-dot/ZnO interface through various spectroscopic and electrochemical techniques. This work could shed light on future application of C-dots in efficient and toxin-free solar water-splitting systems.